Atlantis, the lost empire - Hahn, Don.; Murphy, Tab.; Wise, Kirk.; Walt Disney Pictures; Viva Video Inc. ([Burbank, Calif.] Walt Disney ; distributed in the Philippines by Viva Video, 2002)
Hidden deep below the ocean surface is one of the greatest mysteries of all time--the Lost City of Atlantis. Join the world's most highly qualified crew of experts led by "adventure capitalist" Commander Rourke (Garner) and Milo Thatch (Fox), a linguist who knows the ancient Antlantean language, as they board the incredible 1,000-foot submarine, the Ulysses, and head deep into the mysteries of the sea, hoping to reveal the secrets of Atlantis.
Originally released as a motion picture in 2001.
Editor, Ellen Keneshea ; music, James Newton Howard, Diane Warren.
Featuring the voices of: Michael J. Fox, James Garner, Cree Summer, Don Novello, Phil Morris.
MPAA rating: PG.
VCD, full screen (1.33:1) and widescreen (2.35: 1) presentation; Dolby Digital 5.1 surround sound, THX-certified.
Keywords: Atlantis (Legendary place) -- Drama; Animated films; Feature films; Science fiction films; Fantasy films